2010
DOI: 10.1007/s00268-010-0527-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Peritoneal Dialysis Versus Hemodialysis on Incidence of Intra‐abdominal Infection After Simultaneous Pancreas–Kidney Transplant

Abstract: In our experience, PD prior to SPK transplantation is not associated with increased incidence of intra-abdominal infection compared to HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 22 publications
2
23
2
1
Order By: Relevance
“…Several authors have reported that the use of PD compared to HD before SPKT constitutes a higher risk factor for the development of intra‐abdominal infections, showing an incidence between 23.5% and 44% in PD groups vs 7.7% and 34% in HD groups . However, other studies do not find any significant differences between the groups in the overall incidence of intra‐abdominal infections (9.6%‐28% in PD groups vs 8.8%‐30% in HD groups) . In our series, the overall rate of infections was 71%, and 55 (33%) patients showed intra‐abdominal location with no significant difference between the groups (31.6% in HD vs 35.8% in PD).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Several authors have reported that the use of PD compared to HD before SPKT constitutes a higher risk factor for the development of intra‐abdominal infections, showing an incidence between 23.5% and 44% in PD groups vs 7.7% and 34% in HD groups . However, other studies do not find any significant differences between the groups in the overall incidence of intra‐abdominal infections (9.6%‐28% in PD groups vs 8.8%‐30% in HD groups) . In our series, the overall rate of infections was 71%, and 55 (33%) patients showed intra‐abdominal location with no significant difference between the groups (31.6% in HD vs 35.8% in PD).…”
Section: Discussioncontrasting
confidence: 61%
“…Series comparing PD and HD prior to SPKT have also shown discordant results with respect to patient and pancreas graft survival and the rate of post‐transplant intra‐abdominal infections …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjusted analysis confirmed that pre-transplant dialysis modality does not have an impact on the subsequent development of PTDM [77]. Likewise, PD prior to simultaneous-pancreas-kidney transplantation is not associated with increased incidence of intra-abdominal infection compared to HD [78]. As described, PD may provide several advantages for diabetic patients, while risks should also be taken into account to optimize therapy (Table 1).…”
Section: Peritoneal Dialysis Risks In Diabeticsmentioning
confidence: 97%
“…However, 10 PD patients developed peritonitis [21]. Also, in a series of 100 patients undergoing simultaneous pancreas-kidney (SPK) transplantation (25 PD patients, 75 HD patients) frequency of abdominal infections, one year pancreas-graft survival rates, acute rejection episodes, kidney graft survival rates, or length of hospital stay did not differ between the two groups [25].…”
Section: Pd and Complications After Renal Transplantationmentioning
confidence: 99%